Thyroid hormones and their membrane receptors as therapeutic targets for T cell lymphomas - Cremaschi, Graciela Alicia (2016)
Thyroid hormones (THs) are important regulators of metabolism, differentiation and cell proliferation. They can modify the physiology of human and murine T cell lymphomas (TCL). These effects involve genomic mechanisms, mediated by specific nuclear receptors (TR), as well as nongenomic mechanisms, that lead to the activation of different signaling pathways through the activation of a membrane receptor, the integrin αvβ3. Therefore, THs are able to induce the survival and growth of TCL. Specifically, the signaling induced by THs through the integrin αvβ3 activates proliferative and angiogenic programs, mediated by the regulation of the vascular endothelial growth factor (VEGF). The genomic or pharmacologic inhibition of integrin αvβ3 reduces the production of VEGF and induces cell death both in vitro and in xenograft models of human TCL. Here we review the mechanisms involved in the modulation of the physiology of TCL induced by THs, the analysis of the interaction between genomic and nongenomic actions of THs and their contribution to T cell lymphomagenesis. These actions of THs suggest a novel mechanism for the endocrine modulation of the physiopathology of TCL and they provide a potential molecular target for its treatment.